Análise do fluxo de gases na camada de cobertura do aterro sanitário municipal oeste de Caucaia (ASMOC) - Oliveira, Cláudio André Almeida de (2011)
The growing human consumption entails a greater generation of waste, which, in turn, must be properly treated and disposed. The storage of waste in landfills produces gas, which if not managed properly will affect the quality of life. The uncontrolled emissions of these gases cause multiple economic, social and environmental impacts, as due to air pollution in different cities around the world. The community surrounding the landfill is actually impaired by virtue of living with the constant stench, flammable and even carcinogenic compounds present in the biogas. Worldwide, the uncontrolled release of biogas into the atmosphere is one of the human contributions to the increase of greenhouse gases (GHG) emissions and global warming. One of the main ways to avoid the random passage of the biogas generated in landfills to the atmosphere is to provide an adequate coverage of the waste system, which has, among other functions, prevent the escape of gases and the ingress of rainwater into the mass of waste as well as assist in the collection and treatment of the biogas generated within the landfill. Techniques were developed in the laboratory and field research to consider the flow of gases through the soil used as cover Landfill Metropolitan West Caucaia (ASMOC), to assess the functionality of the cover layer and estimate the amount of gases, methane (CH4) and carbon dioxide (CO2) emitted by the landfill. Four different points on the cell surface were chosen, where two samples were collected, a deformed and other undeformed, for each selected point. The results showed that the covering layer is classified as sandy silt-clay, with permeability of 2,2 x 10-4 cm/s, liquid limit of 27%, plastic limit of 14% (plasticity index: 13%), maximum dry density of 1.83 g/cm³ and optimum moisture content of 11%. The methodology used was the static flow measurement with high sensitivity, which measures the gas flow through the cover layer, using precision instruments. The average flow of CH4 emitted by the layer of coverage ranged between 105 and 1.361 m3/dia.m2, while the average CO2 fluxes ranged 76 - 1.048 m3/dia.m2. The average CH4 flux can reach values close to 9,452 tons / year, which represents about 198 500 tonnes of CO2 eq per year in an area of 78 hectares of the landfill.